Causes of Groundwater Resource Decline in The City of Bandung Perspective of Islamic Economic Law - Sumadi, Hendy (Suhuf: International Journal of Islamic Studies, 2024)
This study aims to examine the causes of the decline in groundwater resources in the perspective of the concept of Islamic economic law, through selected article sources. This research uses a normative doctrinal approach or normative juridical legal research that examines the internal aspects of law or positive regulations. Data collection techniques are carried out through literature studies in the form of secondary data in the form of published articles in journals as basic research material. The condition of the Groundwater Basin (CAT) in Bandung City is now entering a critical condition, one of the visible indications is the decline in groundwater levels by 60-80 percent each year. According to Islamic economic law, everything related to water resources management is believed to be a trust from Allah SWT that must be managed and utilized properly. Islam allows freedom for humans to utilize water resources that are public (general) on the condition that the management must be fair and balanced, not damaging and polluting the environment and natural resources.